Insights of nose to brain delivery in treating Parkinson’s disease: A systematic review - Pranay, Renukuntla; Tatikayala, Ravi Kumar; Damera, Sujatha; Pathakala, Naveen; Jadi, Rajendra Kumar (Creative Pharma Assent, 2024)
Background: In Parkinson's disease (PD), a complicated neurodegenerative ailment, neurons in the substantia nigra that produce dopamine are lost, resulting in an insufficiency of the neurotransmitter that is essential for the regulation of voluntary and smooth muscular movements. This review focuses on the obstacle triggering the effectiveness of traditional PD treatments, which is the blood-brain barrier (BBB), which prevents some therapeutic medicines from reaching the brain. It encompasses the potential strategy of nose-to-brain administration by innovative approaches, including nanoparticles, liposomes, dendrimers, and cell-based carriers, directly delivering the drugs from nose to brain. Methods: The methodology involved examining the characteristics, advantages, applications, and challenges of various nanoparticles like SLNs, Nanoliposomes, Quantum dots, dendrimers, etc., through meticulous analysis of articles including from PubMed (5), ScienceDirect (5), Bentham Science (4) and Scopus databases (5). Conclusion: The review concludes by emphasizing the potential applications of nanoparticles in circumventing the problems encountered with traditional methods of drug administration in treating PD. This detailed study brings to light the applications and the challenges that need to be faced in utilizing nanoparticles for nose-to-brain delivery. Attention is directed towards the enlightenment of advanced carriers that target specific brain regions via the olfactory and trigeminal routes. The drug directly reaches the brain, bypassing BBB.